KAJIAN PENILAIAN TINGKAT KEBERHASILAN REKLAMASI TAHAP OPERASI PRODUKSI DI PT. NAGA KARYA SULTRA DESA MAROMBO KECAMATAN LASOLO KABUPATEN KONAWE UTARA PROVINSI SULAWESI TENGGARA - Filda Oktaviani Erong; Yazid Fanani; Lakon Utamakno (Institut Teknologi Adhi Tama Surabaya, 2022)
Naga Karya Sultra Ltd is a company engaged in nickel mining in Marombo Village, Lasolo District, North Konawe Regency, Southeast Sulawesi Province. Reclamation has become an important part of mining activities, thereby requiring evaluation of its success. This research was aimed at analyzing the implementation of reclamation at the production operation stage and its success rate through a quantitative method approach consisting of land management, revegetation, and maintenance. Based on the Minister of Forestry Regulation No. P. 60/Menhut-II/2009, the success rate of reclamation carried out by Naga Karya Sultra Ltd was categorized as moderate as it reached 85.6. It meant that the reclamation was accepted with a note of improvement. According to the Decree of the Minister of Energy and Mineral Resources No. 1827 K/30/MEM/2018, it obtained 84.5%. After reviewing and considering factors of reclamation success rate, the value obtained was well received.